Dermoscopic features of follicular mycosis fungoides of nonscalp areas: Report of 11 cases and literature review - Mina Saber; Fatemeh Mohaghegh; Elahe Mardani; Farahnaz Fatemi Naeini (Wiley, 2023)
Abstract Background Folliculotropic mycosis fungoides (FMF) is a rare variant of MF that involves hair follicles and requires a more aggressive treatment regime. Significantly, some patients with classic MF can eventually have some degree of follicular involvement. Objectives The aim of this study was to describe the dermoscopic features of FMF in nonscalp areas to facilitate early diagnosis and posttreatment monitoring. Methods The clinical and dermoscopic features in 11 FMF patients were analyzed and compared with the reports in the literature. Results Obliteration of hair follicles, loss of terminal hairs and hair loss were detected in all patients. Follicular accentuation, follicular dilation and broken hairs were found in almost all patients (90.9%). Other common follicular‐based dermoscopic features (<50%) were follicular plugging, perifollicular orange colour, perifollicular erythema and vessels, hyperpigmented halo around the follicle, follicular hyperkeratosis, comedo‐like lesions and perifollicular scales. The most frequent 'dominant' dermoscopic features were follicular accentuation with follicular plugging and dilation of follicular opening. Conclusions Identification of specific distinguishing dermoscopic patterns of FMF not only could be helpful in classifying MF patients but also could provide prognostic information regarding the disease course and aid in therapeutic decisions. In MF patients, dilation of follicular opening and spiky follicular keratosis are considered the most specific dermoscopic features of follicular involvement since they are uncommon in other conditions.